2018
DOI: 10.1016/j.invent.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the implementation of eHealth interventions for informal caregivers of people with dementia

Abstract: ObjectivesThe objectives were to (1) systematically review the literature on the implementation of eHealth interventions for informal caregivers of people with dementia, and (2) identify determinants of successful implementation.MethodsOnline databases were searched for articles about eHealth interventions for informal caregivers of people with dementia, providing information on their implementation. Articles were independently screened and inductively analyzed using qualitative analysis. The analysis was mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 70 publications
(47 reference statements)
2
116
1
Order By: Relevance
“…Another issue that emerged from the three cases concerned the availability of information about activities, organising these in a shared calendar and the use of technology to assist coordination within and among organisations. Uryan, Matusitz, and Breen (2012) showed that digital systems can enhance interorganisational relationships or networks, but this technology must be user friendly, and all information should be kept in one place (Christie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue that emerged from the three cases concerned the availability of information about activities, organising these in a shared calendar and the use of technology to assist coordination within and among organisations. Uryan, Matusitz, and Breen (2012) showed that digital systems can enhance interorganisational relationships or networks, but this technology must be user friendly, and all information should be kept in one place (Christie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further development of the prototype for a future trial will require emphasis on functionality, tailoring abilities and implementation, including organisational determinants of use, how carers would access and learn about the website and the wider context in which the prototype may later work. This has been neglected in previous online-based interventions aimed at family caregivers of people with dementia [51]. This intervention addresses many of the concerns of limited services available for family caregivers of people with dementia in end of life care phases, and concerns that end of life care policy simply focuses on the last days of life [13].…”
Section: Lessons Learnt For Developmentmentioning
confidence: 99%
“…The main resistance for its establishment is given by the three protagonists of the assistance: patients and caregivers, professionals, and mainly the managers of the health administration [40].…”
Section: Social Sanitary Assistance Management Toolsmentioning
confidence: 99%